DATA LEAKAGE IN ICT OUTSOURCING: RISKS AND COUNTERMEASURES (Journal of Information and Communication Technology, 2010)
Having been among the top ranks of worldwide ICT outsourcing indices for a number of years, Malaysia is familiar with the role outsourcing has played in changing today’s business landscape. However, concerns of data privacy and security, and the risks of data leakage arise during the course of outsourcing as the process may involve the exposure or handling of sensitive and confidential client and organization information to outsource providers since the company has little control over its outsourced data when it is in the provider’s possession. Empirical findings on the risks and countermeasures of data leakage are presented, in the context of outsourcing in Malaysia. From the findings, it was apparent that the inherent risks were signifi cant and that the countermeasures were positively correlated to reducing the risks. This study contributes to the limited pool of knowledge on data leakage issues in outsourcing. Organizations engaging in or contemplating outsourcing will find the results beneficial not only in understanding the data leakage concerns but also in supporting the high priority for these concerns to be addressed. However, more effort is required to enforce the countermeasures as prudent precautionary routines to reduce data leakage risks.